2016
DOI: 10.3390/nu8050270
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Balance and Dietary Glycemic Index in Pregnancy Predict Neonatal Body Composition

Abstract: The influence of maternal macronutrient balance and dietary glycemic index (GI) on neonatal body composition has received little study. We hypothesized that the overall quantity and quality of macronutrients, particularly carbohydrate, in the maternal diet could have trimester-specific effects on neonatal growth and body composition in women at risk of gestational diabetes. Maternal diet was assessed using 3-day food records in mid (n = 96) and late (n = 88) pregnancy as part of the GI Baby 3 study. Neonatal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
(54 reference statements)
1
10
1
Order By: Relevance
“…Indeed, the body fatness and fat free mass of newborns in our study were similar to healthy values from normative data [ 47 ]. However, our findings differ from those of a previous small study which showed an inverse association between dietary GI and infant fat free mass in a group of women at risk of GDM [ 48 ]. These differences may relate to the risk nature of the participants or timing of dietary assessment.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, the body fatness and fat free mass of newborns in our study were similar to healthy values from normative data [ 47 ]. However, our findings differ from those of a previous small study which showed an inverse association between dietary GI and infant fat free mass in a group of women at risk of GDM [ 48 ]. These differences may relate to the risk nature of the participants or timing of dietary assessment.…”
Section: Discussioncontrasting
confidence: 99%
“…The results for body composition of the infant may depend on pregnancy stage because of relative changes in infant muscle and adipose tissue insulin sensitivity. In line with this hypothesis, the same group of authors found that, in mid-pregnancy and late-pregnancy, a higher maternal intake of carbohydrate energy or a higher GI was associated with lower infant fat free mass index whereas in late pregnancy higher carbohydrate energy also predicted a lower infant fat mass index [ 63 ]. Although there are no long-term studies, both outcomes bear an increased metabolic risk.…”
Section: Pregnancy Outcomementioning
confidence: 95%
“…However, fetal fat development mainly occurs in late-pregnancy and abdominal circumference is an important indicator of fetal fat deposition [35]. This could suggest that a higher maternal early pregnancy dietary glycemic load may rather affect fetal body composition than growth, which is also suggested by the previous studies conducted in infants [36,37]. Contrary to our prior hypothesis, we observed that a higher maternal early pregnancy dietary glycemic index within a low-to-normal range was associated with lower fetal length growth rates from late-pregnancy onwards and with a lower risk of delivering a large-for-gestational-age infant only.…”
Section: Discussionmentioning
confidence: 88%